Apologia Kristen Bahwa Alkitab Dapat Dipercaya Saat Alkitab Dipertanyakan - Haryanto, Luciana; Sihombing, Mangapul (JURNAL KADESI, 2025)
Apology comes from the root word "apologia", which means defense, or rational explanation to prove that someone is not guilty in court. According to Kalus Stevanus, the word "apologia" and also "apologeomai" in Greek means to defend or be responsible, as well as to defend oneself or be responsible. Apologetics can be understood as a discipline that studies how to take responsibility and how to defend and provide an effective answer to one's beliefs. Apologetics is here to defend Christian philosophy. The Bible is the main source for proving the truth of the Gospel because it is God's own testimony and provides a basis for thought and evidence of the truth of his message. The Bible does not only record the history of Christianity alone. Therefore, the responsibility of a believer is to identify every statement found in the Bible as one truth. In addition, you must bear the responsibility to provide adequate evidence to those who oppose the truth of the Bible. God inspired all the writings of the Bible. Every part of the Bible must be accepted as a divine mandate and guide for every aspect of our lives. The Bible gives us true wisdom, hope, and enlightenment to know and love God our Creator. The Bible is considered by Christians not only to be a trustworthy book, but also to be the sole authority and only source of truth regarding Christian doctrine and practice. Reading and studying the Bible and preaching God's Word daily are essential parts of living our lives as God's people. We must apply the beauty and truth of the Bible to our daily lives